Seizures during high‐dose antidepressant therapy: a case series with clinical and video‐electroencephalography characteristics. Issue 9 (4th September 2013) - Ducharlet, K.; Seneviratne, U.; Sedal, L.; Salzberg, M.; Cook, M.; D'Souza, W.
Abstract: This case series identified drug causes of seizures in patients with depressive disorders. Three patients with seizures were admitted for video‐electroencephalography (EEG) monitoring in the context of high‐dose antidepressants and sodium valproate. Very high‐dose antidepressants caused complex partial seizures with secondary generalisation that gave characteristic EEG discharges. This is the first reported series to capture the ictal EEG features associated with antidepressants.